As correspondências de Clarice Lispector: cartografias de um processo criativo - Silva, Carlos Augusto Moraes (2021)
The exchange of letters between writers is an important object of study for those who are committed to understanding literary practice. The epistolary texts reveal information that goes beyond biographical data and even intimate information of renowned authors. By both Literary Criticism and Literary Historiography, those texts are organized and analyzed in order to answer questions about literary works and authors. They also function as mirrors that reflect different shades of the process of literary conception and creation. In this perspective, the letter is a privileged space, a locus for the construction of thoughts and ideas. This research study highlights Clarice Lispector's letters by considering them as a “laboratory” or na “archive” of literary creation and an important support for the understanding of her fictional work and their aesthetic conceptions. In this study, we found in these manuscripts a detailed work related to the genesis and criticism of fictional texts, we had access to the intricacies of analysis and interpretation, we identified the external motivations that originated Clarice Lispector’s first novels, which are Perto do Coração Selvagem (Near to the Wild Heart) (1943), O Lustre (The Chandelier) (1946), A Cidade Sitiada (The Besieged City) (1949) and A Maçã no Escuro (The Apple in the Dark) (1961).